PENGARUH PENDIDIKAN DAN KEBUDAYAAN TERHADAP JIWA KEAGAMAAN - Nurlila Kamsi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2017)
Education is an effect on a person's religious life, especially in the personal formation or the formation of character. The higher one's education, the better the level of intelligence in performing worship to Allah SWT. Therefore, the effect of education on religious life is important to know in order to instill a sense of religious on a protege. Among its influence is Family Education, Educational Institutions, and education in the community. While religious traditions influence in shaping the experience and consciousness of religion, forming the religious attitude in a person who lives in an environment of a particular religious tradition.